Linking Reflective and Authentic Learning: Encouraging Deeper Learning Experiences in a First-Year Civil Engineering Module at a University in South Africa - Johannes Bester; Erica Pretorius (University of Johannesburg, 2022)
Teaching and learning in higher education still largely use traditional approaches that promote memorisation of content knowledge. These traditional approaches are in stark contrast to the world of work, which encourages problem-solving and higher-order thinking. In a first-year civil engineering concrete technology course, we used reflection on an authentic learning task to encourage a deeper learning experience for students. We hoped that by including reflection and an authentic learning task in the module, students would be more actively engaged with the module content. The research question addressed in this study is: how does reflective practice and an authentic learning activity support student learning in a practical component within a first-year civil engineering module? Reflection should allow students to think deeply about what worked well and what did not during conceptualisation, development and submission of their authentic learning project. This case study collected qualitative data to generate the findings. The data consisted of student reflections during and after completion of the practical component. Students' reflections indicated that the authentic learning task resulted in much deeper learning as opposed to surface learning and memorisation of content knowledge. The results indicate that the reflective exercise encouraged students to think deeply about their learning and on how to improve their skills, knowledge and attitudes throughout the project. Finally, this process shifted the focus from content knowledge dissemination to development of critical thinking and lifelong learning skills.